Ecological relevance of suborganismal and population responses of terrestrial oligochaeta to the fungicide copper oxychloride - Maboeta, Mark Steve (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D)--Stellenbosch University, 2000.